Large Brunner's Gland Hyperplasia with Bleeding: A Case Report. (12th June 2021) - Okutomi, Yuki; Kato, Takaharu; Aizawa, Hidetoshi; Endo, Yuhei; Kasahara, Naoya; Watanabe, Fumiaki; Noda, Hiroshi; Rikiyama, Toishiki
Abstract : We report a rare case of a large Brunner's gland hyperplasia (BGH) with severe anemia. A 33-year-old woman was transferred to our hospital with anemia and a duodenal mass. She had a 2-week history of melena and mild shortness of breath. Her hemoglobin level was 4.9 g/dl, and she required a blood transfusion. Abdominal computed tomography revealed a 7 cm tumor in the descending duodenum, and duodenoscopy revealed a polyp-like tumor with an ulcer at the duodenal bulb. We decided to perform surgery to prevent further bleeding. Intraoperatively, the tumor stalk was located at the anterior wall of the duodenal bulb; the ampulla was not involved, and we resected the tumor with the wall of the duodenal bulb. The resected tumor measured 7.0 × 4.0 × 2.3   cm, and pathologically, the tumor consisted of proliferated Brunner's glands in a small amount of fibrous stroma. The histological diagnosis was BGH with no malignancy. Most cases of BGH are benign and asymptomatic; however, it is important to be aware that some patients have severe anemia, gastrointestinal obstruction, or malignant potential.